2016
DOI: 10.1021/acs.inorgchem.6b02520
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Resonance of Cobalt(II) Trispyrazolylmethanes and Counterion Association

Abstract: Paramagnetic resonance studies (EPR, ESEEM, ENDOR, and NMR) of a series of cobalt(II) bis-trispyrazolylmethane tetrafluoroborates are presented. The complexes studied include the parent, unsubstituted ligand (Tpm), two pyrazole-substituted derivatives (4Me and 3,5-diMe), and tris(1-pyrazolyl)ethane (Tpe), which includes a methyl group on the apical carbon atom. NMR and ENDOR establish the magnitude of H hyperfine couplings, while ESEEM provides information on the coordinatedN. The data show that the pyrazole 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(125 reference statements)
1
10
0
Order By: Relevance
“…5D and E ). Collectively, the data demonstrated that SNHG6 may accelerate melanoma progression by increasing RAP2B expression ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…5D and E ). Collectively, the data demonstrated that SNHG6 may accelerate melanoma progression by increasing RAP2B expression ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…These chemical shifts are consistent with previously-reported spectra of Tp-based Co(ii) complexes. 69,70 The spectrum of 4 is more complex; in addition to the four Tp Me2 -derived features, it displays a series of peaks arising from the CysOEt ligand (marked with the black dots in Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the closed-form expressions above allow us to limit the variable parameters to just the electron relaxation times. For example, our previous work on methyl-substituted derivatives of [Co(Tpm) 2 ]-[BF 4 ] 2 provided NMR-derived (and ENDOR-verified) measures of the contact coupling strengths (A iso ), 14 leaving only T 2e as a variable in eq 2. Similarly, with distances and angles (assuming knowledge of the z-axis direction) defined by the reported crystal structure 34 or a suitable DFT-optimized structure, the only variables in eq 3 are T 1e and T 2e .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The Tpm chemical shifts show slightly less curvature than the corresponding curves for Tp 2 Co over the available temperature range, while our previous work indicated similar levels of contact (isotropic) coupling to the individual protons in the two molecules. 11,14 The one exception was the 3H proton, for which A iso increased sixfold from −0.27 (Tp 2 Co) to −1.5 MHz in the Tpm complex.…”
Section: Apically Appended [Co((tbubzo)tpe) 2 ][Bf 4 ]mentioning
confidence: 99%